Analisis Strategi Peningkatan Penerimaan Pajak Restoran Kota Bekasi Tahun 2020 Di Masa Pandemi Covid-19 (Studi Kasus Pada Badan Pendapatan Daerah Kota Bekasi) - Christy Balencia; Dwikora Harjo (Jurnal Ilmu Administrasi Publik, 2021)
This study is conducted to analyze the Strategy for Increasing Bekasi City Restaurant Tax Revenue in 2020 During the Covid-19 Pandemic at Regional Revenue Agency of Bekasi City. The results of this study indicate where the strategy formulation and implementation in the restaurant tax revenue in its application did not run well, especially during the Covid-19 pandemic. Indeed, in 2018 to 2019 there was an increase by 3.94% but the return there is a decrease in 2020 of 7.7%. In this study, the writer applies theory of strategy by Kotten, which according to him can be classified into four points: organizational strategy, program strategy, resource support strategy, and institutional strategy. A qualitative approach with a descriptive method was used in this study. The data collections in this study were by observation, documentation, and interviews. The results of this study indicate that the strategy for increasing Bekasi City Restaurant Tax Revenue in 2020 did not run well, as can be seen from the failure to achieve the targets that have been set due to the large number of Restaurant Taxpayers who do not know about the SIPDAH program.